2014
DOI: 10.1007/s12544-014-0147-z
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester driver behaviour questionnaire: self-reports of aberrant behaviour among Czech drivers

Abstract: Purpose Considering the human contribution to car crashes, it seems necessary to make a distinction between different forms of aberrant driver behaviour and its different psychological origins. The aim of the present study was to determine the factors that affect driving behaviour, to prepare a factor model, to identify the role of age, gender, kilometres driven per year, and social status, and to examine the relationship between self-reported driver behaviour in DBQ and self-reported accident involvement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…The separate analyses for the private car drivers generally indicated, in accordance with Naevestad et al [50], that peer RSC was the strongest predictor of all safety behaviours, except lacking seat belt use, followed by nationality and national RSC. In accordance with Sucha et al [35], education contributed negatively to aggressive violations and lacking seat belt use, indicating less of these behaviours with increasing levels of education. Gender also contributed negatively, indicating generally less violations among female drivers (cf.…”
Section: Factors Influencing Road Safety Behaviourssupporting
confidence: 88%
See 3 more Smart Citations
“…The separate analyses for the private car drivers generally indicated, in accordance with Naevestad et al [50], that peer RSC was the strongest predictor of all safety behaviours, except lacking seat belt use, followed by nationality and national RSC. In accordance with Sucha et al [35], education contributed negatively to aggressive violations and lacking seat belt use, indicating less of these behaviours with increasing levels of education. Gender also contributed negatively, indicating generally less violations among female drivers (cf.…”
Section: Factors Influencing Road Safety Behaviourssupporting
confidence: 88%
“…About 1. 35 technology, and infrastructure [2]. There are, however, still possibilities for further reductions, but it has been argued that this requires the application of new approaches to road safety.…”
Section: Background and Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of another study which had examined the high risk driving behaviors among taxi drivers in the capital of Iran illustrated that the attitude of drivers toward driving safely was also eligible and most of drivers reported that they always or often don't do high risk driving behavior. In that study three common high risk behavior in drivers included using cellphone during driving, not having proper distance with the car ahead and not driving between the lines (Sucha, Sramkova, & Risser, 2014).…”
Section: Discussionmentioning
confidence: 99%